(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
An attempt was made to examine butterfly proboscis length and their significance in carrying out activities of the butterflies in relation to their nectar plants. Observations were made in seven selected areas (viz. Satchari, Modhupur, Rema-kalenga, Shaltila, Bhawal National Park, and Botanical and Zoological gardens of the Curzon hall area) from July 2014 to June 2015. Thirty four butterfly species of seven families, viz. Hesperiidae, Nymphalidae, Danaidae, Papilionidae, Pieridae, Lycaenidae and Satyridae, were observed. The strategic activities of proboscis in different butterflies were examined when they were used in foraging activity. The proboscis length of butterflies was measured during the study period. Nectar plants were identified in the laboratory. The corolla length of the nectar plants was measured in the field and found a good relation with the proboscis length of the butterflies. Among the observed species, hesperiid butterflies comparatively contain long proboscis, and can visit flowers up to 28 mm long corolla tube. The results obtained, indicate that the butterfly proboscis had significant role in co-evolution between the butterfly species and the flowers of the nectar plants. J. Biodivers. Conserv. Bioresour. Manag. 2017, 3(1): 93-102